Beetroot Juice Supplementation Increases High Density Lipoprotein-Cholesterol and Reduces Oxidative Stress in Physically Active Individuals - Archana Singh,; Saroj Kumar Verma,; Vijay Kumar Singh,; Chindalaga Nanjappa,; Nagraj Roopa,; Pakalpati Srinivas Raju ,; Som Nath Singh, (Journal of Pharmacy and Nutrition Sciences, 2015)
Beetroot juice contains a high level of biologically accessible antioxidants, beneficial phytochemicals and dietary nitrate, which seem to exert beneficial effects in human health. Dietary nitrate, from beetroot has been reported to lower blood pressure. However the impact of beetroot on lipid profile and oxidative stress is unknown. In present study, the effect of supplementation with beetroot juice for 15 days was investigated. Plasma lipid profile, antioxidant status, oxidative stress and body composition changes were evaluated at baseline and after 15 days of beetroot juice supplementation. Beetroot juice supplementation beneficially influenced the lipid profile by significantly increasing the levels of high-density lipoprotein cholesterol (HDL-C) from 42.9 ± 8.3 mg/dl to 50.2 ± 9.8 mg/dl and decreasing low-density lipoprotein cholesterol (LDL-C) from 129.7 ± 82.3 mg/dl to 119.5 ± 79.2 mg/dl compared with baseline values. Beetroot juice supplementation increased (P < 0.05) plasma nitrite level and guanosine 3’, 5’-cyclic monophosphate (c-GMP) levels. A significant increase in plasma total antioxidant capacity and vitamin C levels was observed after beetroot juice intake for 15 days. There was no significant change in the body fat mass and lean body mass of participants with the beetroot juice supplementation. Beetroot juice supplementation significantly decreased the stress markers plasma hydroperoxides and cortisol levels. Beetroot juice acts as a potent vasodilator by increasing plasma c-GMP levels and nitrite levels. Beetroot juice consumption improves plasma lipid profile and antioxidant status, encouraging further evaluation on a population with higher cardiovascular disease risk.